Stability assessment as a criterion of stabilization of the movement trajectory of mobile crane working elements - Kacalak, Wojciech; Budniak, Zbigniew; Majewski, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
The article presents a stability assessment method of the mobile crane handling system based on the safety indicator values that were accepted as the trajectory optimization criterion. With the use of the mathematical model built and the model built in the integrated CAD/CAE environment, analyses were conducted of the displacements of the mass centre of the crane system, reactions of the outrigger system, stabilizing and overturning torques that act on the crane as well as the safety indicator values for the given movement trajectories of the crane working elements.
Keywords: mobile crane; stability of a crane; overturning torque; lifting capacity; tip-over axis